Propuesta de inserción de la lengua de señas como un aporte a la formación profesional de los estudiantes de la carrera en ecoturismo, Universidad Técnica Estatal de Quevedo, año 2019 - Riofrío Holguín, Karol Jessenia (2019)
Ecotourism is an activity that welcomes tourists with different needs and interests, so its professionals must be trained to deal with them. The purpose of this research project was to propose the insertion of sign language into the academic curriculum of the Ecotourism program at the Universidad Técnica Estatal de Quevedo, so that its students in training can manage groups of hearing-impaired people and thus they can develop inclusive tourism. For this, the relationship between the academic units of the professional field was determined, then the acceptance of the teaching was identified and the final inclusive proposal was developed. The results allowed the identification of 8 subjects related to sign language, among which the following units were: Guiding Techniques, Hiking, Community Tourism, Trekking, Public Relations, Tourist Marketing, Hostelry and Human Relations. Subsequently, an analysis was carried out to determine how sign language can be implemented in each of the learning units according to the contents set out in the syllables. And finally, an inclusive proposal was proposed that contains activities that students can carry out with the teacher during fieldwork and classroom work. Keywords: Sign language - LSEC (Ecuadorian Sign Language) - Inclusive tourism – Hearing-impaired people - Ecotourism - Academic Curriculum